Utilization of life feed Alona sp., Boiled Egg Yolk and Commercial Feed Toward Survival Rate of Betta Fish Larvae - Mikraim J. Kaseger; Henneke Pangkey; Diane J. Kusen; Henky Manoppo; Winda M. Mingkid; Nego E. Bataragoa (Sam Ratulangi University, 2019)
The purpose of this study was to find out the survival rates of betta fish larvae (cupang) that were given life feed Alona sp., boiled egg yolk and commercial feed for 21 days. Data analysis was performed by one-way ANOVA, and continued with BNJ (Tukey) test. The result of the survival rate is as follow treatment with life feed Alona sp. 56%, treatment with boiled egg yolk 26%, and treatment with commercial feed 0%. The results of statistical tests show there are significant differences. Significant value p <.0002 (<.05). Water quality parameter measured during the study was temperature of 26 ºC.Keywords: betta fish larvae, life feed, Alona sp., survival rateABSTRAKTujuan penelitian ini adalah untuk mendapatkan laju kelangsungan hidup larva ikan betta (cupang) yang dibeerikan pakan alami Alona sp., rebusan kuning telur dan pakan komersil selama 21 hari. Analisis data dilakukan dengan ANOVA one way, dan dilanjutkan dengan uji BNJ (Tukey). Hasil laju kelangsungan hidup adalah sebagai berikut, perlakuan dengan pakan alami Alona sp. 56%, perlakuan dengan rebusan kuning telur 26%, dan perlakuan dengan pakan komersil 0%. Hasil uji statistik menunjukan adanya perbedaan yang nyata. Nilai signifikan p <.0002 (<.05). Parameter kualitas air yang diukur selama penelitian adalah suhu 26ºC.Keywords: larva ikan betta, pakan alami, Alona sp., kelangsungan hidup